Practical applications of copper-based enzymes: synthesis of sulfonated polyaniline through laccase-catalyzed oxidation - Fabrizi de Biani, Fabrizia; Corsini, Maddalena; Pogni, Rebecca; Baratto, Maria Camilla (Frontiers in Chemistry, 2024)
Known for its tunable conductivity and stability, Polyaniline (PANI) is a valuable polymer for electronics and sensing devices. Challenges in solubility have been addressed by creating sulfonated PANI (SPANI), enhancing its practical use. Synthesizing SPANI from sulfonated aniline is intricate, but laccase biocatalysis offers an eco-conscious solution, effective even against high redox potential obstacles. This research monitored the Trametes versicolor laccase-induced oxidation of 3-ABSa via UV-vis spectroscopy, with a notable peak at 565 nm signifying SPANI synthesis, effective even at suboptimal pH. Mediators further boost this process. Moreover, NMR and spectroelectrochemistry confirm the green synthesis of SPANI by laccase, hinting that pH fine-tuning could improve yields, alongside the concurrent creation of azobenzene derivatives.